Study on Evolution Law and the Mechanical Mechanism of Strong Mine Tremors in a Deep Coal Mine - Chao Wang; Man Wang; Siyuan Gong; Junpeng Zou; Kunbo Wu (Advances in Civil Engineering)
Strong mine tremor occurs frequently in deep mines, which have brought great hidden dangers to the safety of mine production. This paper takes panel 63/06 in No. 6 mining area of Dongtan coal mine as the research background, through geological survey, laboratory test, theoretical analysis, numerical simulation, on-site microseismic monitoring, the seismic evolution law and its mechanical mechanism, etc., and the conclusions are as follows: (1) there are three sets of key layer groups between the surface of the panel 63/06 and the coal seam, among which there is a large amount of energy in the thick Jurassic red layer and the lower key layer, which provides an energy basis for the red-bed to break and generate strong mine tremors; (2) on the plane, most of the strong tremors occurred in front of the mining position of the working face and tended to transfer to the side of the gob, and longitudinal, high-energy mine tremors are mainly distributed in high-level red sandstone; (3) the release location of high-energy mining earthquakes does not match the location of microseismic accumulation, indicating that there is no elastic energy accumulation in the lower surrounding rock before the strong mining earthquake occurs, and it highlights the characteristics of structural occlusal instability rather than energy abrupt instability in the rupture of the red and thick sandstone; and (4) the Dongtan red-bed type strong mine tremors have a large focal rupture radius, a long rupture duration, a small corner frequency, and a weak initial P wave, and the characteristics of low stress drop and no catastrophic nature indicate that the thick and low-strength red-bed is prone to large-scale fractures, which should belong to the structural instability type mine shock dominated by tensile fracture.